Online talks communicating and learning through TED talks. - Tinagan, Gabrielle Rose L.
The advent of technology now influences the integration of modern techniques in teaching and learning as a way of adapting to the times. Given this, teachers should make full use of materials from the Internet and derive benefits from it. The technological experience is one that envelopes and enhances ones emotions and ones senses. Technology will change ones experience of education. This study looks into the perspective of communication teachers in universities in Iloilo City towards TED Talk as an effective medium for teaching and learning. The objectives of this study are to describe TED Talk from the point-of-view of Mass Communication/Communication teachers, to determine if TED Talk videos are favorable to Mass Communication/Communication teachers and finally, to determine the perception of Mass Communication teachers to TED Talk video as an effective medium for learning. Overall, results of the study showed that Mass Communication and Communication teachers have a positive perception to TED Talks as a tool for enhancing learning and communication and is favorable to be used in classroom instructions and discussions.